Visualising anthropomorphism as a creative communicative mode in Samit Basu and Ashish Padlekar’s The Tall Tales of Vishnu Sharma: Panchatantra - Cynthiya Rose J S; Bhuvaneswari R (Creativity Studies)
In today’s ocular-centric era, vision and visuality play a significant role in representing ideas. This article analyses anthropomorphism as a communicative mode that helps readers comprehend a story’s underlying meaning, using a socio-semiotics metafunction as a lens. The study focuses on Samit Basu and Ashish Padlekar’s adaptation of the famous Panchatantra collection, The Tall Tales of Vishnu Sharma: Panchatantra (published in 2015), where creatures with the ability to speak are the central characters. This story emphasises a diverse group of characters from the world of Panchatantra who communicate their problems to Vishnu Sharma, their chosen guardian, through the transformation of animals into humans. Through the use of animated letters, mascots, and anthropomorphic parameters, barriers can be eliminated in a creative approach. The paper underscores the significance of studying signs and interpreting visually represented social phenomena in order to articulate culture, society, and historical context. The research is divided into two sections: the first section explores the function of images by analysing image artefacts that question the presence of anthropomorphism. In contrast, the second section introduces the four degrees of anthropomorphism and their characteristics. The hypothesis posits that anthropomorphism can effectively convey meaning, especially in stories aimed at children. This study seeks to contribute to a greater comprehension of the use of anthropomorphism as a creative mode of communication in contemporary literature.